THE RELATIONSHIP BETWEEN NURSING EDUCATION LEVEL AND YEARS OF EXPERIENCE ON PATIENT SATISFACTION AND HEALTH OUTCOMES IN A PUBLIC HOSPITAL IN SAUDI ARABIA - Fatimah Nassar Alrasheedi, Madihah Saud Al Rasheedi, Shemah Khatim Dawi Alrasheedy, Amani Khatim Dhawi Alrasheed, Theglh Nasar Ayed Al Rashedi, Abdulkarim Saud Al Rasheedi (Chelonian Research Foundation, 2022)
Background: Nursing education and experience are essential factors in providing high-quality patient care and improving patient outcomes. This study aimed to investigate the relationship between nursing education level and years of experience on patient satisfaction and health outcomes in a public hospital in Saudi Arabia. Methods: A cross-sectional study was conducted among 500 nurses working in a public hospital in Riyadh, Saudi Arabia. Data were collected using a structured questionnaire that included demographic information, nursing education level, years of experience, and patient satisfaction and health outcomes. Multiple linear regression analysis was used to examine the relationship between nursing education level and years of experience on patient satisfaction and health outcomes. Results: The majority of nurses had a bachelor's degree (60.2%) and 5-10 years of experience (35.4%). Nursing education level and years of experience were significantly associated with patient satisfaction (β = 0.18, p < 0.001; β = 0.22, p <0.001, respectively) and health outcomes (β = 0.15, p < 0.01; β = 0.19, p < 0.001, respectively). Nurses with higher education levels and more years of experience had higher patient satisfaction and better health outcomes. Conclusion: Nursing education level and years of experience are significant predictors of patient satisfaction and health outcomes. Healthcare organizations should invest in nursing education and training programs to improve patient care quality and outcomes. Keywords: nursing education, nursing experience, patient satisfaction, health outcomes, Saudi Arabia